Evaluating the impact of peer comparison on vancomycin dose order verification among pharmacists. Issue 2 (23rd October 2018) - Nguyen, Cynthia T.; Davis, Kyle A.
Abstract : Purpose: To evaluate the effect of blinded and unblinded peer comparison on appropriateness of vancomycin dose order verification. Methods: This was a single center, prospective, quasi‐experimental study evaluating randomly selected inpatient vancomycin orders over a 6‐month period (January 1, 2017 to June 30, 2017). The interventions consisted of providing peer comparison reports describing the percentage of appropriately verified vancomycin orders based on the individual pharmacist. In intervention phase I, these reports were blinded. In intervention phase II, the reports were unblinded. Both intervention phases were compared with a pre‐intervention control group. The primary outcome was appropriate vancomycin dose order verification, defined as adherence to the institution's vancomycin dosing guideline. Results: One thousand six hundred twenty five vancomycin orders were included for evaluation (537 orders in the control group, 549 orders in intervention phase I, and 539 orders in intervention phase II). The percentage of appropriately verified vancomycin orders were 72%, 76%, and 83% in the control, phase I, and phase II groups, respectively. Unblinded peer comparison was associated with an increase in the percentage of appropriate vancomycin dose order verification (odds ratio, 1.79; 95% confidence interval, 1.36‐2.34). Conclusions: Unblinded pharmacist peer comparison improved vancomycin dose order verification compared with education alone and blinded peer comparison. Further studies are needed to evaluate the effect of this type of intervention for quality metrics at other departments of pharmacy.